HOW THE CREATIVITY AND INNOVATION CAN SUPPORT THE SUSTAINABILITY OF THE EMBROIDERY BUSINESS TO FACE 4.0 COMPETITION - Moh Solehatul Mustofa, Kemal Budi Mulyono (International Journal of Advanced Science and Technology, 2020)
This study explains the importance of innovation and creativity in business for embroidery artisans in order to fight the business competition in 4.0 Industrial Revolution era. This research focus on how embroidery small business located in Central Java, Indonesia can survive the competition through creativity and innovation in business. The respondents in this study were 156 owners or managers of the embroidery small enterprises. The data analysis technique used in this study was Structural Equation Modelling (SEM). The results of this study indicate the importance of business creativity in improving business performance. However, the innovation capability is not able to improve the business performance directly, instead of it improves the business creativity. This study also found the importance of marketing orientation in improving the capability of business innovation and business creativity. Meanwhile, it is necessary to conduct future studies and elaborate the entrepreneurship more deeply, because it is an element of business creativity that can be well-actualized. Keywords: Marketing Orientation, Business Creativity, Innovation, Business performance, Embroidery Small Business